PENGARUH PENGALAMAN KERJA, KARAKTERISTIK INDIVIDU, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA BANK BPD PUSAT BALI - Komang Ayu Marhaeni; Gde Bayu Surya Parwita; Putu Agus Eka Rismawan (VALUES, 2022)
Performance is performance is the result of employee work seen from aspects of quality, quantity, working time, and cooperation to achieve the goals set by the organization. With high performance, employees will feel excited to work so that employees will love their work more and care about the company. The purpose of this study is to determine the effect of work experience, individual characteristics, and job satisfaction on employee performance at Bank BPD Central Bali. The population and sample in the study were 211 people, with the sampling method using the Slovin formula. Data collection techniques used in this study were observation, interviews and questionnaires. The analysis technique used is multiple linear regression, analysis of determination, and t test. The results showed that work experience, individual characteristics, and job satisfaction on employee performance partially had a positive and significant effect on employee performance at Bank BPD Central Bali.